2005
DOI: 10.1037/0278-7393.31.6.1258
|View full text |Cite
|
Sign up to set email alerts
|

Does Retrieval Fluency Contribute to the Underconfidence-With-Practice Effect?

Abstract: Judgments of learning (JOLs) made during multiple study-test trials underestimate increases in recall performance across those trials, an effect that has been dubbed the underconfidence-with-practice (UWP) effect. In 3 experiments, the authors examined the contribution of retrieval fluency to the UWP effect for immediate and delayed JOLs. The UWP effect was demonstrated with reliable underconfidence on Trial 2 occurring for both kinds of JOL. However, in contrast to a retrieval-fluency hypothesis, fine-grained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

6
71
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 71 publications
(81 citation statements)
references
References 15 publications
(42 reference statements)
6
71
2
2
Order By: Relevance
“…The JOLs would be inappropriate because items remembered on Trial 1, even with difficulty, are also likely to be recalled on Trial 2 (Benjamin & Bjork, 1996). In contrast to their expectations, Serra and Dunlosky (2005) did not find selective underconfidence for items that lacked retrieval fluency. Koriat et al (2002) ruled out three plausible explanations of the UWP effect: the underestimation of performance explanation, the study time allocation explanation and the hard-easy effect explanation.…”
contrasting
confidence: 53%
See 3 more Smart Citations
“…The JOLs would be inappropriate because items remembered on Trial 1, even with difficulty, are also likely to be recalled on Trial 2 (Benjamin & Bjork, 1996). In contrast to their expectations, Serra and Dunlosky (2005) did not find selective underconfidence for items that lacked retrieval fluency. Koriat et al (2002) ruled out three plausible explanations of the UWP effect: the underestimation of performance explanation, the study time allocation explanation and the hard-easy effect explanation.…”
contrasting
confidence: 53%
“…Alternatively, immediate JOLs, which do not involve a diagnostic retrieval attempt, do have reason to rely on MPT. In support of the MPT heuristic, have noted that when judgments are delayed, the UWP effect is either reversed (Dunlosky & Connor, 1997;Koriat & Ma'ayan, 2005, Koriat, Ma'ayan, Sheffer & Bjork, 2006, absent Meeter & Nelson, 2003), or extremely truncated (Serra & Dunlosky, 2005). Furthermore, showed that past test performance predicted immediate JOLs, but not delayed JOLs.…”
mentioning
confidence: 84%
See 2 more Smart Citations
“…Some studies involving metacognition focus on only one aspect; for example, the influence of age and sex (SHARMA;LAROIYA, 2008), the metacognitive knowledge (WHITE;FREDERIKSEN, 2005), the metacognitive monitoring (VADHAN; STANDER, 1994), the metacognitive control (ROSS et al, 2006) or a combination of these, referred as metacognitive processes or strategies (KRAMARSKI et al, 2001). These studies were conducted in realistic settings, such as classrooms (VEENMAN;VERHEIJ, 2001;NIETFELD et al, 2005), or in Education or Psychology laboratories (JANG; NELSON, 2005;SERRA;DUNLOSKY, 2005). These investigations contributed with the use of dynamic methods applied to the reality of the classroom and the impacts of these studies are in the presentation of results, that point metacognition as an indispensable item in the dynamics of "thinking".…”
Section: Introductionmentioning
confidence: 99%